Efektivitas aplikasi parenting mobile terintegrasi budaya lokal ngada “nalo” terhadap literasi anak usia dini - Wea, Ludgardis; Fono, Yasinta Maria; Meka, Marsianus; Nafsia, Andi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2026)
Early childhood literacy skills at TKK Generasi Unggul are still low due to the lack of varied and interactive learning media. The purpose of this study is to determine the effectiveness of the mobile-based parenting application